111k views
2 votes
What is (f - g)(x)?
f(x) = 3x?
g(x) = -x? + 4

1 Answer

7 votes

Answer:

(f - g)(x) = 4x - 4

General Formulas and Concepts:

Pre-Algebra

  • Distributive Property

Algebra I

  • Combining Like Terms

Explanation:

Step 1: Define

f(x) = 3x

g(x) = -x + 4

(f - g)(x) is f(x) - g(x)

Step 2: Find

  1. Substitute: (f - g)(x) = 3x - (-x + 4)
  2. Distribute -1: (f - g)(x) = 3x + x - 4
  3. Combine like terms: (f - g)(x) = 4x - 4
User Andriy Makukha
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.